Mortalidade por câncer de pênis: análise de tendência nos estados brasileiros - LISBÔA, Luciana Léda Carvalho (2019)
INTRODUCTION: Cancer is a set of diseases that have in common the disordered growth of cells that invade the tissues and organs, storing themselves for other regions of the body. Penile carcinoma is considered a renal neoplasm, little studied and more frequent in developing countries. OBJECTIVE: To analyze the trend of mortality from pays cancer in the Brazilian states. METHODOLOGY: This is an ecological study, in a time series (1999-2016), describing the records of cases of skin cancer in all units of the eighteenth century, through the Declarations of Death (DO). The data were organized and tabulated in Microsoft Excel 2016 and the STATA version 14 program was used. For the calculations of the rate and mortality coefficient, the total number of deaths due to penile cancer was calculated by the number of deaths in men and the total number of deaths for penile cancer Created by the total male population in one period, respectively. The reference data were collected in the information of the 2000 and 2010 Censuses and the intercensity projections, on the IBGE website. The trend analysis was performed using the Prais-Winsten regression model. RESULTS: White men represent a percentage of 46.10% of deaths. The predominant age group was cancer deaths between the 60s and 79s (39.21%). Regarding marital status, the men were married (49.88%). The most frequent schooling was 1 to 3 years of formal study, with 23.33%. Penicillin cancer mortality rate, considering the two phases of the studied rhythm, increased significantly in the state of Tocantins (5.28 - 12.86), followed by Acre (0 - 6.64) and Maranhão (6.17 - 11.51). Regarding the Penile Cancer Mortality Coefficient, the most advanced state among the time series was Tocantins (2.36 - 6.83). They correspond to the North and North Regions, then the Northeast and Southeast. The North region was observed the highest rate of variation (7.46%) and not the Southeast minor (1.09%). CONCLUSION: This review of data was opened to a number of national studies on growth cancer, which was already underway. There is a need to try to differentiate and strengthen national policies that prevent prevention and prevention.